Water decontamination via nonradical process by nanoconfined Fenton-like catalysts - Tongcai Liu; Shaoze Xiao; Nan Li; Jiabin Chen; Xuefei Zhou; Yajie Qian; Ching-Hua Huang; Yalei Zhang (Nature Communications, 2023)
Abstract There is an urgent need to develop effective and sustainable solutions to reduce water pollution. Heterogeneous Fenton-like catalysts are frequently used to eliminate contaminants from water. However, the applicability of these catalysts is limited due to low availability of the reactive species (RS). Herein, nanoconfinement strategy was applied to encapsulate short-lived RS at nanoscale to boost the utilization efficiency of the RS in Fenton-like reactions. The nanoconfined catalyst was fabricated by assembling Co3O4 nanoparticles in carbon nanotube nanochannels to achieve exceptional reaction rate and excellent selectivity. Experiments collectively suggested that the degradation of contaminants was attributed to singlet oxygen (1O2). Density functional theory calculations demonstrated the nanoconfined space contributes to quantum mutation and alters the transition state to lower activation energy barriers. Simulation results revealed that the enrichment of contaminant on the catalyst reduced the migration distance and enhanced the utilization of 1O2. The synergy between the shell layer and core-shell structure further improved the selectivity of 1O2 towards contaminant oxidation in real waters. The nanoconfined catalyst is expected to provide a viable strategy for water pollution control.